Analisis Proses dan Nilai Hata- Hata Mambere Podah dalam Perkawinan Adat Simalungun - Waruwu, Ermina; Sumbayak, Diana Pramita; Br. Sipayung, Siti Fatimah; Manik, Pahala (Universitas Hamzanwadi, 2019)
The Simalungun tribe has a tradition of carrying out wedding ceremonies. One of the traditions carried out is the hata-hata mambere podah. The problem of this research is how the marriage process of the Simalungun custom, how the hata-hata mambere podah, and how the value contained in the hata-hata mambere podah at the Simalungun traditional wedding ceremony. This study aims to analyze and describe the traditional marriage process of Simalungun, hata-hata mambere podah and the values contained in the hata-hata mambere podah in the process of the marriage of the traditional Simalungun. This study used a descriptive qualitative approach and data was collected using interview methods with recording techniques. The research instrument is the interview guide that is used to interview informants consisting of traditional leaders, residents, brides and residents who have received hata-mambere podah. Data that has been collected was analyzed using qualitative analysis with the content Analysis method.Keywords : Process; Values; Hata-hata mambere podah; The marriage of Simalungun custom.